Study on Sound Transmission across a Floating Floor in a Residential Building by Using SEA - HUANG, Xianfeng; LU, Yimin; QU, Chen; ZHU, Chenhui (Archives of Acoustics, 2021)
For the purpose of reducing the impact noise transmission across floating floors in residential buildings, two main sound transmission paths in the floating floor structure are considered: the stud path and the cavity path. The sound transmission of each path is analysed separately: the sound transmission through the cavity and the stud are predicted by statistical energy analysis (SEA). Then, the sound insulation prediction model of the floating floor is established. There is reasonable agreement between the theoretical prediction and measurement, and the results show that a resilient layer with low stiffness can attenuate the sound bridge effect, resulting in higher impact noise insulation. Then, the influences of the floor covering, the resilient layer and the floor plate on the impact sound insulation are investigated to achieve the optimised structure of the floating floor based on the sound insulation.